Development and Psychometric Evaluation of the Malaysian Pharmacoethics Instrument - Pei Lin, Lua; Sazrina, WZW; Majeed, ABA (2014)
This study aimed to devise an instrument based on the Malaysian Code of Conduct for Pharmacists and Bodies Corporate for the measurement of ethical practices among community pharmacists in Malaysia, and to test its validity and reliability. A set of questionnaire was designed and refined via an expert group discussion and statistical analysis. It contains four sections; personal information, pharmacy information, undergraduate training information and profession-related questions. The latter section was scored on 5-point Likert scale. The instrument was administered to 32 randomly-chosen community pharmacists (male=12, female=20; majority age-ranee=31-35years; bumiputra=30; married=25). Data was analysed using SPSS for Windows version 12.0. Validity of the instrument was examined by performing exploratory factor analysis. Its internal consistency reliability was measured via Cronbach's alpha value while test-retest reliability was assessed by intraclass correlation coefficient. Four main factors were extracted from 33 items in the profession-related section (explaining 46.4 % of total variance); which emerged under four themes identified as Business Practice, Ethical Practice, Professional Practice and Personal Attitude. After deletion of one unstable item, Cronbach's alpha values were 0.730 (Business Practice), 0.80 (Ethical Practice), 0.71 (Professional Practice) and 0.66 (Personal Attitude). The test-retest intraclass correlation coefficient values were 0.80 (Business Practice), 0.80 (Ethical Practice), 0.74 (Professional Practice) and 0.73 (Personal Attitude). These results indicate early evidence of the instrument's validity and reliability for use in Malaysia. As such, the study of pharmacoethics among community pharmacists holds a promising future with the generation of this new instrument.